EVALUATION OF CHITOSAN QUALITY FROM SHRIMP, CRAB, AND BLUE SWIMMING CRAB WASTE: YIELD, WATER CONTENT, AND DEGREE OF DEACETYLATION: EVALUASI KUALITAS KITOSAN DARI LIMBAH UDANG, KEPITING, DAN RAJUNGAN: RENDEMEN, KADAR AIR, DAN DERAJAT DEASETILASI - Pratiwi, Fika Dewi; Notonegoro, Hartoyo; Syaputra, Denny (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Mud crab, blue swimming crab, and vannamei shrimp carapace are crustacean wastes that have not been optimally utilized in Bangka Island and have the potential to pollute the environment. Converting the biomass from this waste into chitosan supports the principles of a circular economy. This study evaluates the quality of chitosan produced from crustacean waste based on yield, moisture content, and degree of deacetylation (DD), and compares two FTIR-based methods for estimating DD using the spectral band ratios A1320/A1420 and A1655/A3450. Carapace waste (100 g) was processed through demineralization (1.5 M HCl), deproteinization (3.5% NaOH), and deacetylation (60% NaOH) with two replications per species. The chitosan yields were 4.0% ± 0.5 (mud crab), 8.7% ± 0.5 (blue swimming crab), and 12.4% ± 0.9 (shrimp), respectively. The water content was still within the limits of SNI 7949:2013 (<12%), namely 6.4% ± 2.0, 10.7% ± 2.7, and 6.3% ± 0.6. Based on the A1320/A1420 ratio, the DD values were 86.8% ± 0.4, 84.4% ± 0.1, and 95.3% ± 2.5, respectively, all exceeding the minimum standard of 75%. In contrast, the A1655/A3450 method produces much lower DD values ​​(<75%). These findings indicate that local crustacean shell waste has strong potential as a source of high-quality chitosan. FTIR is a practical method for DD estimation, but it still needs further validation, especially with standard methods such as 1H-NMR.